DETERMINATION OF WATER TARIFFS PDAM TIRTA PEUSADA EAST ACEH, INDONESIA: A STUDY OF THE ELEMENT OF GHARAR - Canden Chairani Isrumuharram; Delfi Suganda; Safwan Kamal (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2024)
The determination of water tariffs by Perumda Tirta Peusada in East Aceh District has led to community dissatisfaction due to tariffs that are considered unfair and do not reflect the quality of service received, as well as unclear water distribution. This issue potentially contains elements of gharar (uncertainty) in the water sale and purchase transaction, which is contrary to the principles of Islamic law. This research uses descriptive analysis method with a case study approach and qualitative research, by collecting data through interviews and literature study to analyse the implications of water tariff setting at Perumda Tirta Peusada in the context of sharia economic law. The determination of water tariffs by Perumda Tirta Peusada in East Aceh Regency contains elements of gharar in the context of sharia economics, because the tariff charged is not in accordance with the volume of water consumed by customers. Customers are still charged for 10 cubic metres even though their water usage is less than that amount, creating uncertainty in the transaction. In addition, frequent water distribution disruptions and supply instability further exacerbate this problem, as customers pay for services they do not receive as expected. This practice goes against the principles of transparency, fairness, and clarity advocated in Islamic law. Therefore, Perumda Tirta Peusada needs to improve its tariff policy and the quality of water distribution to ensure that water transactions are more fair, transparent, and in accordance with sharia principles.